Comparative phylogeography of small mammals across the Great Plains Suture Zone highlights repeated processes of speciation and community assembly coincident with the 100th meridian - Herrera, Thomas M. (Kansas State University, 2022)
Accelerating anthropogenetic environmental change is globally impacting species' distributions, resulting in altered eco-evolutionary trajectories with the potential to cause severe disruption to ecosystem stability and human health. Ameliorating impacts of biotic turnover requires management of species as well as their interactions. Therefore, it is crucial to understand how past environmental change influenced the evolutionary history of species and regional assemblages. The Great Plains presents a novel system for diagnosing both evolutionary histories and community assembly of North American mammals. By encompassing the middle third of North America, the Great Plains supports mammal faunas from both western and eastern communities, which meet at the peripheries of their ranges, providing insight into the ecological history of multiple communities through evolutionary time. With no physical barriers and geographic complexity, it is an unexplored but ideal region for understanding evolutionary and ecological histories driven almost solely by environmental change. I couple comparative phylogeography with ecological niche models to investigate the evolutionary history of ten small mammal species that belong to eastern, central, and western assemblages co-distributed across the Great Plains. I assess (1) intraspecific diversification across the Great Plains, (2) congruence of species histories considering regional origins, and (3) the location of regional biodiversity hotspots for both historic and emerging eco-evolutionary interactions. Bayesian phylogenies were estimated from mitochondrial DNA, and Last Glacial Maximum (LGM) niche models were estimated using bioclimatic layers. Given the diverse number of biogeographic contact zones associated with the Great Plains suture zone, I hypothesized species will possess a shared history across the Great Plains regardless of regional and ecological associations. Intra-specific phylogeographic breaks based on current distributions showed broad-scale clustering in the southern Great Plains for eastern, central, and western species. LGM niche models showed that Great Plains small mammals with different regional origins occupied distinct refugia but with a region of contact between assemblages maintained in the southern Great Plains. The combined evidence strongly suggests the southern Great Plains is a hotspot for both diversification within species and long-term interactions among distinct communities and points towards repeatable environmental processes across the Great Plains Suture Zone reciprocally driving diversification and assembly through time.
Keywords: Historic biogeography; Secondary contact; North America; Ecological niche modeling; Faunal element; Soft barrier